2016
DOI: 10.1073/pnas.1607220113
|View full text |Cite
|
Sign up to set email alerts
|

For blacks in America, the gap in neighborhood poverty has declined faster than segregation

Abstract: Black residential segregation has been declining in the United States. That accomplishment rings hollow, however, if blacks continue to live in much poorer neighborhoods than other Americans. This study uses census data for all US metropolitan areas in 1980 and 2010 to compare decline in the neighborhood poverty gap between blacks and other Americans with decline in the residential segregation of blacks. We find that both declines resulted primarily from narrowing differences between blacks and whites as oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 37 publications
2
83
0
Order By: Relevance
“…22 In addition, we found a disproportionate number of black enrollees in the most disadvantaged neighborhoods. Although the segregation of black Americans in disadvantaged areas has been extensively described, 23 Our findings agree with multiple prior studies that have found an independent relationship between neighborhood disadvantage and various health outcomes. A recent study using the ADI measure indicated that individuals in more disadvantaged neighborhoods have a 70 percent greater chance of hospital readmission than those in less disadvantaged neighborhoods even after adjustment for individual factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…22 In addition, we found a disproportionate number of black enrollees in the most disadvantaged neighborhoods. Although the segregation of black Americans in disadvantaged areas has been extensively described, 23 Our findings agree with multiple prior studies that have found an independent relationship between neighborhood disadvantage and various health outcomes. A recent study using the ADI measure indicated that individuals in more disadvantaged neighborhoods have a 70 percent greater chance of hospital readmission than those in less disadvantaged neighborhoods even after adjustment for individual factors.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we found a disproportionate number of black enrollees in the most disadvantaged neighborhoods. Although the segregation of black Americans in disadvantaged areas has been extensively described, our work extends this literature to the MA population. However, the relationship between ADI and our health outcomes did not vary by race.…”
Section: Discussionmentioning
confidence: 90%
“…Gini coefficients associated with the curves were calculated for the NICU segregation index and NICU inequality index for each racial or ethnic group. This approach is based on the method used by Firebaugh and colleagues 2 and Farrell and colleagues 21 for measuring segregation and inequality of income across residential neighborhoods.…”
Section: Methodsmentioning
confidence: 99%
“…Black American history is rooted in racial injustice and there are countless efforts made to counteract a legacy of oppression. Blacks are disproportionately affected by poverty [1], mass incarceration [2], infant mortality [3], limited health care access [4], and health-related conditions including heart disease [5], diabetes [6], stroke [7], kidney disease [8], respiratory illness [9,10], and human immunodeficiency virus (HIV) [11]. Many are well versed in this marginalized status and possess first-hand accounts of the devastating impact of social injustice that permeates through communities.…”
Section: The Black Immunity Mythmentioning
confidence: 99%